2009
DOI: 10.1007/s11243-008-9183-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding and cleavage studies of chiral Mn(III) salen complexes

Abstract: Chiral bridge-substituted manganese(III) complexes of N,N 0 -bis-(2-hydroxynaphthalene-1-carbaldehyde)-(1R,2R)-(-)-diaminocyclohexane and N,N 0 -bis-(2-hydroxynaphthalene-1-carbaldehyde)-(1S,2S)-(?)-diaminocyclohexane have been synthesized. The interaction of these complexes with calf thymus DNA(CT-DNA) was investigated by spectroscopic, thermal denaturation studies, circular dichroism (CD), and viscosity measurements. Results of spectroscopic and viscosity measurements suggest that the two complexes bind to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…From K SV data external binding with moderate intercalation was speculated. Similar types of observation were found with Mn-salen complexes [40]. …”
Section: Fluorescence Spectroscopic Studiessupporting
confidence: 86%
“…From K SV data external binding with moderate intercalation was speculated. Similar types of observation were found with Mn-salen complexes [40]. …”
Section: Fluorescence Spectroscopic Studiessupporting
confidence: 86%
“…17,18 Some manganese complexes, e.g. [Mn(TMPyP)](OAc) 5 (TMPyP = meso-tetrakis(4-N-methylpyridinumyl) porphyrinato), 19 manganese-salen derivatives, 20,21 [Mn(L) 23 also present intercalative DNA-binding capacity or significant DNA/antitumor activity. Therefore the synthesis and characterization of new manganese complexes are of great importance not only for developing novel chemotherapeutics and highly sensitive diagnostic agents but also for understanding the role and mechanism of manganese complexes in biological system.…”
Section: Introductionmentioning
confidence: 99%
“…Salen-Mn complexes possess ability to bind with free-radicals like hydrogen peroxide decomposition, superoxide anion (O2 - ) dismutase, catalase, water oxidation and ribonuclease reduction, and DNA and proteins. It has been reported that Salen-Mn (III) has strong antioxidant activity [ 25 ], moreover, it has the DNA binding and cleavage activity [ 26 , 27 ]. Mn(III)-salen complexes are shown to possess superoxide dismutase (SOD) and catalase activities and are considered as synthetic SOD mimics [ 28 ].…”
Section: Discussionmentioning
confidence: 99%